Concentrated Growth Factors as an Ingenious Biomaterial in Regeneration of Bony Defects after Periapical Surgery: A Report of Two Cases - Nivedhitha Malli Sureshbabu; Kathiravan Selvarasu; Jayanth Kumar V; Mahalakshmi Nandakumar; Deepak Selvam (Hindawi Limited, 2019)
The overall success of a periapical surgery is assessed in terms of regeneration of functional periradicular tissues. The regenerative potential of platelets has been well documented. This article describes the use of concentrated growth factors (CGF), a new family of autologous platelet concentrates, as a sole material for bone regeneration after periapical surgery. 32- and 35-year-old female patients diagnosed with Ellis Class IV, an open apex in 11 with apical periodontitis in 11 and 12 and previously root canal-treated 31 and 41 with a chronic apical abscess, respectively, were managed with endodontic surgery. Subsequent to apicectomy and retrograde filling, the CGF fibrin block and membrane were used before suturing. There was uneventful healing during the immediate post-op and the subsequent follow-up periods. CGF is produced by a differential centrifugation process that results in the formation of a denser fibrin matrix richer in growth factors than those observed in PRF. Reasonable osseous healing was seen as early as 6-month follow-up, thereby recommending the use of CGF as an alternative to bone grafts and membranes in extensive periapical lesions to enhance bone regeneration and to decrease the healing time.